Determinants of Women’s Participation in Self-Help Group (SHG)-Led Microfinance Programme of Bihar Rural Livelihoods Promotion Society (JEEViKA) - Ajesh Palayi, Pramod Kumar; Rabindra Nath Padaria (Indian Journal of Extension Education, 2023)
Bihar Rural Livelihoods Promotion Society (JEEViKA) has been instrumental in improving the depth and coverage of SHG led Microfinance in Bihar in recent years. The study identifies the major determinants of women’s participation in self-help group led microfinance programme of JEEViKA. Motivation by JEEViKA personnel and access to loan have emerged as the prominent reasons for joining self-help group by members as per Garrett’s Ranking Technique.The reasons, as a channel of implementation of schemes and the political involvement/support by PRIs(Panchayati Raj Institutions) have been identified as the least influential factors. Analysis using Logit Model has revealed that the factors, Motivation by JEEViKA personnel and awareness about JEEViKA have a significant positive influence on women’s participation in this programme.